Guardians of the dinasty - Millett, Richard (Library of Congres, /Estados Unidos, 1977)
In this well-documented and scholarly study Richard Millett details the history of the military and political life of twentieth-century Nicaragua. He focuses particularly on the 1920s and 1930s, the formative period of the United States-sponsored Guardia Nacional and of the guardia-backed Somoza dictatorship.The guardia grew out of the U.S. military intervention in Nicaragua which lasted in one form or another from 1912 to 1933. United States officials sought to stabilize Nicaraguan politics by replacing its inefficient and highly politicized army with an effective and politically neutral force. The result was a military which was much more efficient but which was from the first intensely politicized. It brought stability, but at the